Housing and health: A multidimensional, qualitative analysis of the experiences of asylum seekers and refugees living in German reception centres - Eilin Rast; Maren Hintermeier; Kayvan Bozorgmehr; Louise Biddle (Elsevier, 2024)
Objectives: Housing is an important social determinant of health, but the perspectives of asylum seekers and refugees (ASR) in large, centralised reception centres remain under-researched. We therefore sought to examine which housing aspects in reception centres are deemed relevant for health by ASR in Germany. Methods: Based on 47 interviews with 42 ASR in Germany originating from three different studies, we conducted a secondary qualitative analysis. We mapped interview transcripts onto existing housing frameworks and generated four central themes regarding the relationship between housing and health in reception centres. Results: Housing affected ASR health in four key ways: 1) Material conditions, including crowding, hygiene conditions and inability to secure doors, created and exacerbated physical and mental health issues, 2) the unpredictability and instability of housing impeded integration and disrupted social and professional support networks, 3) through forced residential assignment and limited autonomy, ''homemaking'' is severely constrained, leading to worsened mental health, and 4) reception centres do not make sufficient accommodations for individuals with specific medical needs. Conclusion: This study offers a broad perspective on the relationship between ASR reception centres and health. It is evident that this housing context is not conducive to health. Instead, centralised accommodation facilities exacerbate existing health conditions through excessive overcrowding, insufficient infrastructure and the inability to meet health-related needs. Stressful living environments and frequent transfers further burden psychosocial health by impeding a sense of belonging and comfort and by disrupting social and care networks. Current accommodation policy and practice need to be reconsidered to safeguard the health of ASR.